The influence of workplace incivility towards individual outcomes in private and government sector, Kota Kinabalu, Sabah - Enja Anak Manie (2010)
The purpose of this study is to have a greater understanding on the influence of workplace incivility on individual outcomes in private and government sectors in Kota Kinabalu, Sabah. The quantitative research methods been applied in this study to gather data from employees who work in Kota Kinabalu area. In this study, workplace incivility will be the independent variable and individual outcomes in term of behavior and psychological distress as the dependent variable. The workplace incivility scale questionnaire (Cortina et al, 2001) is chosen and adapted to measure the independent variable. While Job Withdrawal Scale (Hanisch & Hulin, 1991) and Scoring Key - General Well-Being (Veit & Ware, 1983) is used to measure dependent variables. In this study, researcher found that workplace incivility has significant relationship with individual outcomes. Moreover, the present study also indicated there are significant differences in experiencing workplace incivility between management and non-management employees. The finding also indicates that there are significant differences in workplace incivility done by superior(s) and peer(s). Most of the respondent also agree that superior(s) more probability to be the instigator of workplace incivility compare to peer(s). Result also indicates that there is a significant difference in the perception of workplace incivility between men and women where female perceive workplace incivility greater than men. Researcher also found that marital status does moderate the relationship of workplace incivility and individual outcomes.